Réponses

2013-11-02T20:24:09+01:00
N= (a+5)(2a+3)+(a+5)(3a-5)
=(a+5)(2a+3+3a-5)
=(a+5)(5a-2)

O= (3b+2)(3b-2)+5b(3b-2)
=(3b-2)(3b+2+5b)
=(3b-2)(8b+2)

P=(y-5)(3y+4)-(y-5)(4y-3)
=(y-5)(3y+4-4y+3)
=(y-5)(-y+7)
2013-11-02T20:36:00+01:00
Bonsoir
Pour factoriser, tu repères les facteurs qui sont communs

N= (a+5)(2a+3)+(a+5)(3a-5);
N = (a+5)(2a+3)+(3a-5)
N = (a+5)(2a+3+3a-5)
N = (a+5)(5a -2)

O= (3b+2)(3b-2)+5b(3b-2);
O = (3b-2)(3b+2)+5b
O = (3b-2)(3b+2+5b)
O = (3b-2)(8b+2)

P=(y-5)(3y+4)-(y-5)(4y-3)

P = (y-5)(3y+4) - (4y -3)
P = (y-5)(3y +4 -4y +3)
P = (y-5)(-y +7)